Effective restoration measures in river‐floodplain ecosystems: Lessons learned from the 'Wilde Mulde' project. Issue 1 (7th March 2022) - Schulz‐Zunkel, Christiane; Seele‐Dilbat, Carolin; Anlanger, Christine; Baborowski, Martina; Bondar‐Kunze, Elisabeth; Brauns, Mario; Gapinski, Cedric M.; Gründling, Ralf; Haaren, Christina von; Hein, Thomas; Henle, Klaus; Junge, Frank W.; et al.
Abstract: Over the last 40 years, a growing number of restoration projects have been implemented to improve the ecological conditions of highly degraded rivers and their floodplains. Despite considerable investment in these projects, information is still limited about the effectiveness and the success of such river restoration measures, mainly due to a lack of standardised and interdisciplinary assessment approaches. During the project 'Wilde Mulde—Restoration of a dynamic riverine landscape in Central Germany', we implemented hydromorphological restoration measures (installation of large wood, removal of rip‐rap, reconnection of a former river side‐arm) along a lowland river in Central Germany. We carried out intensive scientific monitoring of biodiversity, hydromorphology, ecosystem functions and services, as well as socio‐economic aspects. A Before/After‐Control/Impact (BACI) design was used to identify the spatial and temporal effects of the restoration measures and to distinguish them from changes caused by background variation. For this, we used a comprehensive set of indicators, including abiotic (flow velocity, diversity of riverbed topography, and flow resistance), biological (ecosystem respiration, macroinvertebrates, fish, carabids, vegetation, and birds) and socio‐economic (acceptance and public awareness) indicators as well as the ecosystem service indicator aesthetic quality of the landscape. To meet the inherent challenges of such a large‐scale field experiment, like unpredictable environmental conditions, we used an experimental approach that allowed us to demonstrate a measurable success of the implemented restoration measures. The majority of the abiotic and some of the biological and socio‐economic indicators at the restored sites approached values of a natural reference site while already deviating from values of a nonnatural reference site two years after restoration. In addition to the applied interdisciplinary approach, multiple scales of field investigations and data analyses are essential as key components for evaluating successful river and floodplain restoration projects.